A discontinuous Poisson–Boltzmann equation with interfacial jump: homogenisation and residual error estimate. Issue 12 (1st December 2016) - Fellner, Klemens; Kovtunenko, Victor A.
Abstract : A nonlinear Poisson–Boltzmann equation with inhomogeneous Robin type boundary conditions at the interface between two materials is investigated. The model describes the electrostatic potential generated by a vector of ion concentrations in a periodic multiphase medium with dilute solid particles. The key issue stems from interfacial jumps, which necessitate discontinuous solutions to the problem. Based on variational techniques, we derive the homogenisation of the discontinuous problem and establish a rigorous residual error estimate up to the first-order correction.